Soil health and microplastics: a review of the impacts of microplastic contamination on soil properties - Chia, Rogers Wainkwa; Lee, Jin-Yong; Jang, Jiwook; Kim, Heejung; Kwon, Kideok D. (Journal of soils and sediments, 2022)
Purpose Soil is a thin coating of matter that covers the earth’s surface, formed through the process of rock weathering. It is a natural filter for impurities in groundwater and is very important to human health. Recently, some studies from around the world have confirmed that the presence of microplastics in soil is increasing. However, most of these studies only examined the impacts of soil microplastic contamination one or two soil health indicators, rather than study all three soil health indicators at once. Methods In this review, we selected papers published internationally in the past decade and examined the trend of the effects of soil microplastic contamination on all three soil health indicators. Results and discussion Soil microplastic contamination resulted in either an increase or decrease in the trend of the effects on physicochemical and biological soil properties. In other cases, microplastic contaminants do not affect soil properties. The alteration of soil health properties by microplastics was associated with a couple of reasons such as microplastic concentrations and types, changes in soil mechanics and microorganisms. Conclusions The current impact and severity of soil microplastic contamination on soil health properties are expected to persist for a long time, especially with increasing global plastic production. Therefore, more research is required to continuously assess the impact of microplastic contamination on other indicators of soil health that has not been studied previously.